Assessment of Bacterial Aerosols in a Herbal Processing Plant - Karol Bulski; Krzysztof Frączek (Atmosphere, 2023)
The aim of this study was to assess bacterial aerosols in a herbal processing plant in Poland. Bioaerosol measurements of indoor and outdoor air of the herbal processing plant were performed in four measurement rounds, in a seasonal cycle—in spring, summer, autumn, and winter—using a six-stage Andersen’s cascade air sampler. At each measuring point, during the bioaerosol sampling, the values of relative humidity and air temperature were simultaneously measured using the Kestrel 4000 device, and the concentration of particulate matter (fractions 1.0 μm, 2.5 μm, 4.0 µm, and 10.0 µm) using a DustTrak II dust analyzer. The results showed that the production process affects the bacterial aerosol concentrations in the tested plant. There were statistically significant differences in the concentrations of bacterial aerosol between indoor and outdoor air, and between production rooms, taking into account the seasons of the year. The concentrations of bacterial aerosol in the production rooms did not exceed 7.6 ×·103 cfu·m−3 and were lower than the permissible concentration values proposed for production rooms contaminated with organic dust. The calculations showed a significant correlation between the concentration of bacterial aerosol and air temperature. Qualitative analysis of microorganisms isolated from the air of production rooms showed the dominance of Gram-positive cocci of the genus Micrococcus and spore-forming rods of the Bacillus genus. The study confirmed that herbal processing plants may be related to exposure to microbiological agents.